極域雪氷試料におけるダスト濃度分析法の改良と試料保存過程によるダスト濃度への影響 - 三宅, 隆之; ミヤケ, タカユキ; 山田, 廣宣; ヤマダ, ヒロノブ; 東, 久美子; アズマ, クミコ; 倉元, 隆之; クラモト, タカユキ; 平林, 幹啓; ヒラバヤシ, モトヒロ; 本山, 秀明; モトヤマ, ヒデアキ; et al. (2014)
P(論文) 極域雪氷試料を対象として，ダスト分析過程および分析管理の改良と，保存過程によるダスト濃度への影響の評価を行った．ダスト分析過程と分析管理の改良では，校正曲線変更に伴う粒径区分とパルス電圧閾値の変更，繰り返しの分析精度とワイパーのブランク濃度の確認，標準粒子測定によるセンサー感度変動管理を行った．ダスト分析用試料の保存容器の検討の結果，パッキンなしの15mlガラス瓶で，ダスト濃度への影響が最も低かった．ドームふじ氷床コア試料による冷蔵，凍結保存過程の検討の結果，冷蔵保存によるダスト濃度への影響は，1年間で，分析精度以内の4%以下の減少に留まった．凍結保存ではその前後でダスト濃度の増加傾向が見られ，粗大粒子の割合は減少した．これらは，凍結・融解の際のダスト粒子の変化や試料保存容器の材質などの影響が考えられる．またダスト濃度への分散剤添加の影響は，冷蔵，凍結保存に対して，明らかに保存状態を向上させているとはいえなかった． We sought to improve the analytical methods employed when operating a laser particle counter and to evaluate the influence of the storage processes on dust concentrations in polar snow and ice samples. We corrected the particle size ranges and threshold voltage using the new calibration curve, confirmed the analytical precision and dust concentrations of blank of wipers using in a clean room, and managed any variations in the laser sensor's sensitivity by measuring standard particles. The 15 ml glass screw bottles without packing (liner of cap of bottles) yielded the lowest dust concentration of the blank among two types of bottles and nine types of packing for dust analysis. Storage of samples of the Dome Fuji ice core (Antarctica) in a refrigerator for 1 year resulted in just a 4% decrease in dust concentration, which is within the analytical precision of the laser particle counter. Storage in a freezer resulted in an increase in dust concentrations and a decrease in the ratio of large particles more than 0.98 μm in particle diameter in the samples, suggesting a change in dust particle size during storage and an influence by the materials of the storage bottles. The addition of dispersants to the Antarctic snow samples is not clearly suitable when analyzing dust concentrations after sample storage by refrigeration or freezing． departmental bulletin paper